Students' satisfaction with the availability of e-resources, infrastructure, staff commitment and students involvement in colleges of education in Northeastern Nigeria - Bulama, Umar Bizi (2016)
The study attempted to examine the students‘ satisfaction with the availability of eresources, students‘ satisfaction with the availability of infrastructure, students‘ satisfaction with the staff commitment and students‘ involvement in using the e-resources in Colleges of Education in Northeastern Nigeria. This is a descriptive correlational study and using questionnaires as the instruments. The study covers 5 colleges of education, and only NCE level 3 students were involved in Northeastern Nigeria, which gives the total population (N) of 439. Out of 439 students population, 406 were chosen samples and convient sampling technique. The SPSS version 22 was used to run the analysis. Descriptive analysis was used to determine the level of students‘ satisfaction with the availability of e-resources is moderate (M = 2.75; SD= 0.57), student‘s satisfaction with the availability of infrastructure is low (M =1.09; SD= 0.56), students‘ satisfaction with the staff commitment is moderate (M = 3.11; SD= 0.71) and the students‘ involvement in using the e-resources is also at a moderate level (M = 3.10; SD= 0.70). An independent sample t-test was conducted to compare the difference in students‘ satisfaction with the availability of e-resources based on gender. The findings show that there is no significant difference in the mean scores for males (M=2.31; SD= 0.68) and that of females (M=2.31; SD= 0.69); t (406) = 3.42, p =.001. The analysis shows that there is a significant difference in age groups on students‘ satisfaction with the availability of e-resource (F (2, 403) = 11.109, p = .000). Therefore, the Post-Hoc Multiple comparison test based on Tukey HSD indicated a significant difference between the respondents in age groups of 18 – 24 year (M = 2.53, p< .05); respondents with age groups of and 25 – 31 years (M = 2.53, p< .05); and 32 years and above (M= 6.70, p < .05). The analysis revealed that there is a significant difference in college groups on students satisfaction with the availability of e-resources (F (4, 401) = 60.009, p = .000). Thus, the Post-Hoc Multiple comparison based on Tukey HSD revealed a significant difference between the respondent in college groups of COE Hong (M = 3.42, p< .05); COE Azare (M = 3.42, p< .05); COE Gashua (M = 6.20, p< .05); COE Zing (M = 3.93, p>.05); and COE Biu (M = 2.55, p< .05). Also, the findings indicated that there is a weak and significant relationship between students‘ satisfaction with the availability of e-resources and infrastructure in colleges of education (r= .192, p<.05); there is a medium and significant relationship between students satisfaction with the availability of e-resources and staff' commitment in colleges of education (r = .455, p < .05); and there is a medium and significant relationship between students‘ satisfaction with the availability of e-resources and students‘ involvement in Colleges of Education (r = .430, p <.05). However, based on the findings of this study, there is a need to improve the students‘ satisfaction with the availability of e-resources in Colleges of Education in Northeastern Nigeria. Also, the needs to improve the students‘ satisfaction with the availability of infrastructure, students‘ satisfaction with the staff commitment and students‘ involvement in using the e-resources among students in Colleges of Education in Northeastern Nigeria in order to meet up with the needs and demands of the students.